Analysis Of The Influence Of Service Quality And Asn Discipline On Community Satisfaction In The Manufacture Family Card (Kk) Online System In Perigi Baru Village - Apriansyah, Hendi; Salam, Rahmat (INFOKUM, 2022)
This study aims to determine the influence analysis of service quality and ASN discipline on community satisfaction in making online system family cards (KK) in Perigi Baru Village. This research method uses a quantitative approach by distributing questionnaires to respondents and then the data results are processed with the help of the SPSS 25 application. This research has the result that there is a partial influence between service quality on community satisfaction with a t count of 2.149 > t table of 2.069 and a significance of 0.034 < 0.05, there is a partial effect of ASN discipline on community satisfaction with a t-count value of 6.766 > t-table 2.069 and a significance of 0.000 <0.05, there is a simultaneous influence of service quality and ASN discipline on community satisfaction with an F-value of 83.253 > F table value of 3.403 and a significance of 0.000 <0.05